Tratamento de incertezas na priorização de portfólio de projetos de tecnologia da informação: uma abordagem multicritério híbrida - Pariz, Maria Carolina (2019)
The elaboration of the portfolio of information technology (IT) projects is a complex decision process that involves the analysis of qualitative and subjective criteria. Decision making is characterized by the uncertainty of subjective and imprecise assessments resulting from estimates of the data representing the criteria analyzed. A model was proposed to reduce the uncertainties in the selection of IT projects, based on a multicriteria hybrid method composed by the Best Worst Method to establish the weights of the criteria and Fuzzy-TOPSIS to define the ranking of the projects. The model allows (1) to define strategic subcriteria, (2) to adjust the weights according to the reality of the company, (3) to deal with the uncertainties of the evaluations of the decision makers and (4) to obtain the ranking of the projects that translate reality for the distribution of resources in the IT sector. Finally, an application of the model in the IT sector of a Brazilian Agroindustrial Cooperative is presented to demonstrate the applicability of the proposed approach. For managers, the method provides an accurate decision aid tool. Although the model has been applied for the prioritization of IT projects in a cooperative, the same can be generalized to IT sectors of other companies.